Common Hepatic Branch of Vagus Nerve-Dependent Expression of Immediate Early Genes in the Mouse Brain by Intraportal L-Arginine: Comparison with Cholecystokinin-8 - Yamada, Daisuke; Koppensteiner, Peter; Odagiri, Saori; Eguchi, Megumi; Yamaguchi, Shun; Yamada, Tetsuya; Katagiri, Hideki; Wada, Keiji; Sekiguchi, Masayuki (Frontiers in Neuroscience, 2017)
Information from the peripheral organs is thought to be transmitted to the brain by humoral factors and neurons such as afferent vagal or spinal nerves. The common hepatic branch of the vagus (CHBV) is one of the main vagus nerve branches, and consists of heterogeneous neuronal fibers that innervate multiple peripheral organs such as the bile duct, portal vein, paraganglia, and gastroduodenal tract. Although previous studies suggested that the CHBV has a pivotal role in transmitting information on the status of the liver to the brain, the details of its central projections remain unknown. The purpose of the present study was to investigate the brain regions activated by the CHBV. For this purpose, we injected L-arginine or anorexia-associated peptide cholecystokinin-8 (CCK), which are known to increase CHBV electrical activity, into the portal vein of transgenic Arc-dVenus mice expressing the fluorescent protein Venus under control of the activity-regulated cytoskeletal-associated protein (Arc) promotor. The brain slices were prepared from these mice and the number of Venus positive cells in the slices was counted. After that, c-Fos expression in these slices was analyzed by immunohistochemistry using the avidin-biotin-peroxidase complex method. Intraportal administration of L-arginine increased the number of Venus positive or c-Fos positive cells in the insular cortex. This action of L-arginine was not observed in CHBV-vagotomized Arc-dVenus mice. In contrast, intraportal administration of CCK did not increase the number of c-Fos positive or Venus positive cells in the insular cortex. Intraportal CCK induced c-Fos expression in the dorsomedial hypothalamus, while intraportal L-arginine did not. This action of CCK was abolished by CHBV vagotomy. Intraportal L-arginine reduced, while intraportal CCK increased, the number of c-Fos positive cells in the nucleus tractus solitarii in a CHBV-dependent manner. The present results suggest that the CHBV can activate different brain regions depending on the nature of the peripheral stimulus.